Psychoeducational Therapy To Increase Self Efficacy In Patients With Pulmonary Tuberculosis - hapipah; Tedy Mahendra Efendi; Istianah; Irwan Hardi (Jurnal Kesehatan dr. Soebandi, 2023)
Pulmonary Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Pulmonary TB can be cured with treatment carried out for 6-8 months. To achieve recovery, the patient must have good self-efficacy so that he will be motivated to recover and strengthen himself to complete the treatment. During TB treatment various problems, both physiological and psychological, can arise, one of which is related to self-efficacy. Increasing self-efficacy during the treatment period is important so that management of psychoeducational therapy is needed. This study to determine the effect of psychoeducational therapy on self-efficacy in pulmonary TB patients in the work area of ​​the Gerung Health Center. This study uses a quantitative research type with the One Group Pre-Post Test Design approach. The sample in this study were 16 people. The research instrument was the GFCSES (Guide For Constructing Self Efficacy Scale) to measure self-efficacy in pulmonary TB patients. Data analysis with Paired T Test. The results showed a p-value of 0.000 (<α 0.05), so it can be concluded that there is a significant effect between psychoeducational therapy on self-efficacy in pulmonary TB patients in the working area of ​​the Gerung Public Health Center. Based on the results of this study, it is necessary to include material related to psychological changes such as self-efficacy in pulmonary TB patients during the treatment process provided by health workers through education carried out in activities at the family integrated service post or health services. Psychoeducational therapy can increase self-efficacy in pulmonary tuberculosis patients Keyword: Psychoeducational therapy, self efficacy, pulmonary TB